2010
DOI: 10.2215/cjn.03890609
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Health-Related Quality of Life among Hemodialysis Patients in the United States

Abstract: Background and objectives: Health-related quality of life (HRQOL) is a measure of the well being of hemodialysis patients and an independent prognostic predictor. Our aim was to determine whether HRQOL among hemodialysis patients has changed over time.Design Conclusions: Most HRQOL domains showed either no statistically significant change or statistically but not clinically significant change over almost a decade. These results suggest that, despite important developments in hemodialysis care since 1997, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
(24 reference statements)
0
47
0
Order By: Relevance
“…Depressive symptoms, common in the dialysis population, double a patient's likelihood of death (53). Importantly, QOL trends in a sample of the U.S. dialysis population remained unchanged between 1997 and 2006, despite the previously described trends toward early start during a comparable period of time (54).…”
Section: Quality-of-life Benefits Of Early Dialysismentioning
confidence: 95%
“…Depressive symptoms, common in the dialysis population, double a patient's likelihood of death (53). Importantly, QOL trends in a sample of the U.S. dialysis population remained unchanged between 1997 and 2006, despite the previously described trends toward early start during a comparable period of time (54).…”
Section: Quality-of-life Benefits Of Early Dialysismentioning
confidence: 95%
“…In the United States, the majority are treated with in-center hemodialysis (2). Patients receiving hemodialysis have a higher mortality rate and reduced quality of life compared with the general population (2,3). Although there has been some reported improvement in survival in recent years (2,4), studies have shown no improvement in quality of life (3).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment time is also a clinical determinant that when associated with factors such as advanced age, female gender, low level of schooling, unemployment and low income can affect QoL (11,12). Some studies have not identified significant changes in QoL in relation to HD treatment time (13,14). However, the presence of concomitant comorbidities presented a negative correlation with the QoL domains, justifying the reduced values evidenced by these patients, which improved in some domains one year after starting HD (15).…”
Section: Introductionmentioning
confidence: 99%